Students' Perceptions of the Use of Tiktok on the @Zelynafah Account in Improving Vocabulary - Puspanyindra, Wukir Ristawu; Johan, Andrian Nuriza; Triana, Juita (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study investigates the perceptions of eleventh-grade students at SMK PN 2 Purworejo regarding the effectiveness of the TikTok account @zelynafah in enhancing their English vocabulary. With the rise of social media as a significant educational tool, this research aims to explore how platforms like TikTok can facilitate language learning. Utilizing qualitative research methods, semi-structured interviews were conducted with 19 students to gather insights into their experiences and opinions about the content provided by @zelynafah. The findings reveal that a majority of students perceive the account as an effective resource for vocabulary acquisition, appreciating its engaging and interactive format. However, some students expressed concerns about the depth and comprehensiveness of the content. The study highlights the potential of TikTok as a supplementary tool in language education while emphasizing the need for a balanced approach that combines engaging social media content with traditional learning methods. These insights contribute to the growing body of literature on the intersection of social media and language education, offering valuable implications for educators seeking to enhance vocabulary learning in the digital age.